TINJAUAN YURIDIS HAK PENGELOLAAN PEMERINTAH KOTA BATAM ATAS TANAH HASIL REKLAMASI (STUDI PADA HPL YANG DIKELOLA PEMERINTAH KOTA BATAM) - MAHVIRA SIREGAR (PREMISE LAW JURNAL, 2013)
ABSTRACT Law No. 27/2007 on the Management of Coastal Area and Small Islands states that what it means by Reclamation is people’s activities to improve the use of land resources, viewed from environment and socio-economy by filling up the land with soil and drying the land or drainage. The Government Regulation No. 46/2007 is on Batam Free Area and Free Trade in which the government stipulates that Batam is functioned as Free Trade Area and Free Port. It is also stipulated the transfer from HPL of Batam Authority to HPL of Exploiting Body of Batam Free Trade Area and Free Port because institutionally Batam Authority, with this government regulation, transfers Batam Authority to the Exploiting Body of Batam Free Trade and Free Port, including HPL of Batam city Administration which was “transferred” to HPL of the Exploiting Body of Batam Free Trade Area and Free Port. It means that at that time there was the establishment two dualism of the government authority. It is recommended that the Batam city Administration and Batam Authority make correct joint regulation, agreed by both of them to manage the reclaimed land because both parties, according to the Government Regulation No. 8/1953, the Presidential Degree No. 41/1973, in conjunction with the Presidential Decree No. 94/1998, are HPL subjects.   Keywords: Management Rights of Batam city Administration, Reclaimed Land